Pengaruh Beban Kerja Dan Fleksibilitas Kerja Terhadap Kepuasan Kerja Dengan Motivasi Sebagai Pemediasi - Tetty H Sitorus; Harlyn, L Siagian (Yayasan Baru Haji Samsudin, 2023)
The COVID-19 pandemic has changed economic conditions, and companies must adapt to increasingly sophisticated technology. To achieve the set targets, the company assigns workloads to employees. However, a heavy workload can affect employees' physical and emotional well-being. Therefore, companies must set work standards and provide flexibility to increase employee job satisfaction. Employee job satisfaction is essential because it will affect their performance. One aspect that can increase job satisfaction is motivation. Therefore, this research examined the effect of workload and work flexibility on job satisfaction, with motivation as a pemediasi . Researchers used qualitative research with an explanatory approach. Descriptive statistical analysis is a statistical analysis technique used in this study. Primary data sources are from authors who come from respondents who complete questionnaires in a Google form. The results of the survey show that workload and motivation have a positive effect on job satisfaction. But Work Flexibility has no impact on Job Satisfaction. Workload and work flexibility affect motivation. If it is mediated by stimulation, then workload does not affect job satisfaction, but Job Flexibility influences job satisfaction. Simultaneous tests show that Workload and Work Flexibility positively affect Job Satisfaction mediated by motivation.